El poder ante la crisis gobernabilidad en México - Mercado Maldonado, Asael; Germán García-Rivas Garduño, Germán (Nómadas. Critical Journal of Social and Juridical Science, 2011)
This article aims to explain the operation of power as a fundamental element of the state structure to which it belongs, highlighting the focus of Edgar Bodenheimer applying his vision to the interpretation of political and social phenomena that occur in Mexico. As crisis of governance, corruption, violence, every day growing power of drug trafficking, acts of impunity and the growth of extreme poverty. The theory argues that legal history is the history of the struggle for power. The law is the intermediary between anarchy and despotism. The relationship between unequals is subordination and among peers is of law.
Keywords: Law; power; status; despotism; anarchy; crisis; totalitarianism